Good Practice Report : Assuring Learning Outcomes and Standards : Final Report. - Freeman, Mark; Ewan, Christine (Office for Learning and Teaching, 2014)
This final report looks at learning outcomes and standards. Indicators of course quality have traditionally been limited to measures like progression, retention and student experience. Student achievement of intended course learning outcomes has recently attracted interest as an additional indicator. External benchmarking extends the richness and potential of this indicator for driving improvements. Since 2012, all Australian higher education providers have been bound to demonstrate to TEQSA that they meet the Threshold Standards (in the Higher Education Standards Framework). Several standards relate to discipline learning standards, namely in course design, assessment and external benchmarking. Extensive standards work has been undertaken, much of it in Australia and OLT funded. To assist providers, professional bodies, discipline communities and OLT to better comprehend the 'standards landscape', its relationship to student experience, curricula and future development priorities, this work needs cataloguing and synthesizing. A good practice report will support dialogue and the decisions needed to ensure Australian higher education providers produce quality graduates who are valued by employers.